Characterization of PVA-Enzyme Coated Indicator Electrodes GA coated again with PVC-KTpClPB-o-NPOE UV-Vis analysis, variable signal analysis, sensor sensitivity and SEM-EDS - Abd Hakim S (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to characterize the phosphate buffer and urease enzymes through UV-Vis and SEM-EDS absorbance spectra using tungsten as an indicator electrode. The method used is a potentiometric biosensor with urease enzyme immobilization technique for urea analyte. A small detection range of 10-5-10-4M has been studied with PVA-enzyme coated indicator electrodes coated with PVC-KTpClPB. On this basis, the researchers increased the detection range by analyzing glutaraldehyde (GA) mixed with PVA-enzyme and o-NPOE mixed with PVC-KTpClPB. The best results of GA mixed PVA-enzyme at GA2.9% UV-Visible analysis. The best results were PVA-enzyme coated indicator electrodes coated with GA coated again with PVC-KTpClPB-o-NPOE SEM-EDS analysis on PVA-enzyme samples 3x coated with GA 1x and PVC-KTpClPB-o-NPOE 1x with o-NPOE variation of 61% and 66%.